Experimental, numerical and analytical modeling of heat transfer of gravity driven dense particle flow in vertical heated plates. (15th May 2022) - Wei, Gaosheng; Huang, Pingrui; Pan, Longfei; Cui, Liu; Xu, Chao; Du, Xiaoze
Highlights: The heat transfer coefficients between dense particle flow and vertical heated plates were experimentally studied. A numerical model and an analytical model were developed for the wall-to-particle heat transfer. A semi-empirical correlation for the overall wall-to-particle heat transfer coefficient was derived. The reduction of the width of flow channel and the mean particle diameter can improve the wall-to-particle heat transfer. Abstract: The heat transfer coefficient between the gravity driven dense particle flow and vertical heated plates is one of important parameters for the design and optimization of shell-and-plate moving packed bed heat exchangers. This paper gives extensively study on heat transfer between gravity driven dense particle flow and vertical heated plates by combined experimental, numerical, and analytical methods. The wall-to-particle heat transfer coefficients between silicon carbide particles and heated plates are experimentally tested in the designed heat transfer apparatus by varying the mass flow rates of particles with three mean particle diameters (0.207 ∼ 0.364 mm) and different widths of particle flow channel (4 ∼ 10 mm). A numerical calculation model and an analytical model are also established based on plug flow assumption, and compared with the experimental data. The results show that both of the two models exhibit a good agreement with the experimental results when estimating the overall wall-to-particle heat transfer coefficient. However, the numerical calculation model can obtain a more accurate description of the temperature profile than the analytical model attributes to the consideration of the effect of vertical heat diffusion. At last, a new semi-empirical correlation for estimation of overall wall-to-particle heat transfer coefficient was derived based on the analytical solution. Within the test scope of this study, the mean error and maximum error of this new correlation is 3.2% and 9.8%, respectively. The results also show that the reduction of the width of flow channel and the mean particle diameter contributes to the improvement of the wall-to-particle heat transfer coefficient. Graphical abstract: Image, graphical abstract